ANALISIS STRATEGI PEMBELAJARAN KOOPERATIF BERBANTUAN MEDIA ARTICULATE STORYLINE MATERI PENERAPAN NILAI-NILAI PANCASILA PADA PEMBELAJARAN PKN KELAS 5 DI SDN KARANGREJO 4 - Nahdiah Nur Fauziah; Amaza Ilmil Mufidah; Erma Fatmawati; Mu`allimin (STKIP Subang, 2026)
This study aims to analyze cooperative learning strategies supported by Articulate Storyline media in teaching the application of Pancasila values in fifth-grade Civic Education (PKn) classes at SDN Karangrejo 4. This study employs a qualitative approach with a case study design to examine the integration of methods, media, teaching materials, and learning resources. Data were collected through observation, in-depth interviews, and documentation, then analyzed using thematic analysis. The results indicate that the integration of cooperative learning and digital media creates interactive, collaborative, and meaningful learning, characterized by active student engagement, structured group work, the use of contextual teaching materials, and the utilization of digital learning resources and real-world environments. These findings reveal that the success of learning is not determined solely by the method but by the synergy among learning components that enhance understanding and the internalization of Pancasila values. The novelty of this study lies in the holistic analysis of learning strategies within a real-world context, as well as its contribution to enriching technology-based Civic Education (PKn) research and providing practical implications for teachers.